Microbiological Quality and Risk Assessment for Aflatoxins in Groundnuts and Roasted Cashew Nuts Meant for Human Consumption - Modupeade Christianah Adetunji; Ogechi Precious Alika; Ngozi Precious Awa; Olusegun Oladimeji Atanda; Mulunda Mwanza (Journal of Toxicology)
Nuts are one of the commonly consumed snacks but poor handling and storage practices can make them prone to foodborne infections. The study aimed at assessing the microbiological quality and risk assessment for aflatoxins in groundnuts and cashew nuts consumed in selected locations in Nigeria. The moisture content, colony counts, incidence of pathogenic bacteria, aflatoxin contamination, and risk assessment for aflatoxins were evaluated using standard methods. The moisture content and total viable count ranged from 5.00–8.60% and 5.5–89 × 103 cfug−1, respectively, while the fungal count was between 4–24 × 103 and 1.0–4.5 × 102 cfug−1, respectively. Eleven fungal species belonging to 5 genera were isolated from the nuts, with Aspergillus flavus, Rhizopus oryzae, and Fusarium oxysporum having the highest percentage occurrence of 50%. In addition, the aflatoxin concentration ranged 0.1–6.8 and 29–33.78 ng kg−1 for cashew nuts and groundnuts, respectively. The margin of exposure (MOE) to aflatoxin contamination was 6.10 for groundnuts and 1000 for cashew nuts and the nuts consumers were at a risk of exposure to foodborne diseases and aflatoxin contamination with mean exposure values of 27.96 and 0.17 ng kg−1bwday−1, respectively. The risk of primary liver cancer for groundnuts and cashew nuts consumers was also estimated to be 1.38 and 0.01 canceryear−1100,000−1person, respectively. This calls for mitigation measures from appropriate governmental organizations.